Case Report: A Case of Trimethoprim/Sulfamethoxazole-Triggered Hypotensive Shock: Cytokine Release Syndrome Related to Immune Checkpoint Inhibitors and Drug-Induced Hypersensitivity Syndrome - Urasaki, Tetsuya; Ono, Makiko; Mochizuki, Toshiaki; Takeda, Koichi; Nishizawa, Aya; Fukagawa, Eri; Fujiwara, Motohiro; Komai, Yoshinobu; Kitano, Shigehisa; Yuasa, Takeshi; Yonese, Junji; Takahashi, Shunji (Frontiers in Oncology, 2021)
Currently, only a few reports exist on the cytokine release syndrome (CRS) as one of the severe immune-related adverse events (irAEs) induced by immune checkpoint inhibitors (ICIs). Notably, it is very rare that grade 4 CRS related to ICI therapy overlaps with the drug-induced hypersensitivity syndrome (DiHS). A 46-year old woman with metastatic kidney cancer had grade 3 interstitial pneumonitis induced by four cycles of combination therapy of anti-programmed death-1 and anti-cytotoxic T lymphocyte-4 antibodies after right cytoreductive nephrectomy. Prophylactic administration of trimethoprim/sulfamethoxazole (TMP/SMX) was started concomitantly with prednisolone therapy to treat the interstitial pneumonitis. She developed hypotensive shock when reducing the dosage of prednisolone, and required intubation and ventilation using vasopressors at the intensive care unit. She subsequently exhibited prominent leukocytosis and an increased level of C-reactive protein, suggesting markedly increased cytokine levels. Interestingly, facial edema and erythema increased in association with pyrexia, leukocytosis, liver dysfunction, and renal failure, suggesting that she developed DiHS. She received hemodialysis three times, a plasma exchange, and anti-interleukin-6 therapy to treat severe renal dysfunction, a thrombotic thrombocytopenic purpura-suspected condition, and possible grade 4 CRS, respectively. Although these therapies did not elicit sufficient effects, high-dose administration of intravenous immunoglobulin was successful. With steroid mini-pulse therapy and the subsequent administration of prednisolone, she recovered successfully. To the best of our knowledge, this is the first report that ICIs and TMP/SMX can induce hypotensive shock accompanied with CRS and DiHS during immunosuppressive therapy for an irAE. Importantly, the prophylactic administration of TMP/SMX should be performed cautiously to avoid severe drug reactions such as CRS or DiHS.